2019
DOI: 10.1042/ns20180201
|View full text |Cite
|
Sign up to set email alerts
|

The dietary flavonoid isoliquiritigenin is a potent cytotoxin for human neuroblastoma cells

Abstract: Neuroblastoma (NB) is the most common extracranial solid tumor of early childhood; it accounts for approximately 8-10% of all childhood cancers and is the most common cancer in children in the first year of life. Patients in the high-risk group have a poor prognosis, with relapses being common and often refractory to drug treatment in those that survive. Moreover, the drug treatment itself can lead to a range of long-term sequelae. Therefore, there is a critical need to identify new therapeutics for NB. Isoliq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
(100 reference statements)
2
7
0
Order By: Relevance
“…All of these findings confirm that 4HC treatment leads to ROS-induced cell death in MYCN -amplified NB cells. This is consistent with our previous study showing that another chalcone, ISLQ, induced cell death in MYCN -amplified NB cells through the elevation of ROS levels, which was fully prevented by pretreatment with NAC [40]. This is an important finding, as the ability of ROS to chemosensitize cancer cells depends on the basal ROS levels in these cells.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…All of these findings confirm that 4HC treatment leads to ROS-induced cell death in MYCN -amplified NB cells. This is consistent with our previous study showing that another chalcone, ISLQ, induced cell death in MYCN -amplified NB cells through the elevation of ROS levels, which was fully prevented by pretreatment with NAC [40]. This is an important finding, as the ability of ROS to chemosensitize cancer cells depends on the basal ROS levels in these cells.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we found that 4HC exerted potent cytotoxic effects on MYCN -amplified SK-N-BE (2) and IMR-32 human NB cells at low concentrations, in comparison to other non- MYCN -amplified NB cells, kidney embryonic cells, or healthy murine primary neuronal cultures. We also found that the cytotoxicity induced in MYCN- amplified NB cell lines by 4HC was higher than that induced by ISLQ, another chalcone which we had investigated in a previous study [40]. The cytotoxic effect of 4HC treatment was found to be both time- and concentration-dependent and to be accompanied by decreases in both somal and nuclear area.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations